EFISIENSI ENERGI KAYU PADA PROSES PENGERINGAN PAPAN (Waod energy efficiency on timber drying) - Tjutju Nurhayati (Jurnal Penelitian Hasil Hutan, 1993)
The purpose of this research is to study the efficiency wood utilization as an energy source on timber drying. The research was conducted at big and medium scale industries of sengon (Paraserianthes falcataria) wood working which used steam boiler and air duct-fired stove, respectively and at small industry of ramin (Gonisthyllus bancanus) wood working which usedhot water-fired stove.The result indicated that the highest wood/waste energy efficiency obtained was 53 % from big, scale sengon industry which used slabs and trimmings waste as energy source and the lowest one was 14.20% from medium sengon industry.